A Method for Solving the Variational Inequality Problem and Fixed Point Problems in Banach Spaces - Wongvisarut Khuangsatung; Atid Kangtunyakarn (My University, 2021)
The purpose of this research is to modify Halpern iteration’s process for finding a common element of the set of solutions of a variational inequality problem and the set of fixed points of a strictly pseudo contractive mapping in q-uniformly smooth Banach space. We also introduce a new technique to prove a strong convergence theorem for a finite family of strictly pseudo contractive mappings in q-uniformly smooth Banach space. Moreover, we give a numerical result to illustrate the main theorem.
Keywords: Optimization and Variational Analysis